Autophagy induction impairs migration and invasion by reversing EMT in glioblastoma cells. Issue 8 (13th May 2015) - Catalano, Myriam; D'Alessandro, Giuseppina; Lepore, Francesca; Corazzari, Marco; Caldarola, Sara; Valacca, Cristina; Faienza, Fiorella; Esposito, Vincenzo; Limatola, Cristina; Cecconi, Francesco; Di Bartolomeo, Sabrina
Abstract : Cell migration and invasion are highly regulated processes involved in both physiological and pathological conditions. Here we show that autophagy modulation regulates the migration and invasion capabilities of glioblastoma (GBM) cells. We observed that during autophagy occurrence, obtained by nutrient deprivation or by pharmacological inhibition of the mTOR complexes, GBM migration and chemokine‐mediated invasion were both impaired. We also observed that SNAIL and SLUG, two master regulators of the epithelial–mesenchymal transition (EMT process), were down‐regulated upon autophagy stimulation and, as a consequence, we found a transcriptional and translational up‐regulation of N‐ and R‐cadherins. Conversely, in BECLIN 1‐silenced GBM cells, an increased migration capability and an up‐regulation of SNAIL and SLUG was observed, with a resulting decrease in N‐ and R‐cadherin mRNAs. ATG5 and ATG7 down‐regulation also resulted in an increased migration and invasion of GBM cells combined to an up‐regulation of the two EMT regulators. Finally, experiments performed in primary GBM cells from patients largely confirmed the results obtained in established cell cultures. Overall, our results indicate that autophagy modulation triggers a molecular switch from a mesenchymal phenotype to an epithelial‐like one in GBM cellular models. Since the aggressiveness and lethality of GBM is defined by local invasion and resistance to chemotherapy, we believe that our evidence provides a further rationale for including autophagy/mTOR‐based targets in the current therapeutical regimen of GBM patients. Highlights: We were able to prove that autophagy modulates cell migration. We show that autophagy modulation affects invasion of glioblastoma cells. We provide evidence that some key EMT players are modulated by autophagy.